Apresentação PBCIB n.1, v.12, 2017. - Freire, Gustavo Henrique de Araújo; Freire, Isa Maria; Araújo, Vânia Rodrigues Hermes de (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2017)
Apresentação PBCIB n.1, v.12, 2017.